Optical and Electrochemical Properties of Self-Organized TiO2 Nanotube Arrays From Anodized Ti−6Al−4V Alloy - Fraoucene, Henia; Sugiawati, Vinsensia Ade; Hatem, Djedjiga; Belkaid, Mohammed Said; Vacandio, Florence; Eyraud, Marielle; Pasquinelli, Marcel; Djenizian, Thierry (Frontiers in Chemistry, 2019)
Due to their high specific surface area and advanced properties, TiO2 nanotubes (TiO2 NTs) have a great significance for production and storage of energy. In this paper, TiO2 NTs were synthesized from anodization of Ti-6Al-4V alloy at 60 V for 3 h in fluoride ethylene glycol electrolyte by varying the water content and further annealing treatment. The morphological, structural, optical and electrochemical performances of TiO2 NTs were investigated by scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), UV-Visible spectroscopy and electrochemical characterization techniques. By varying the water content in the solution, a honeycomb and porous structure was obtained at low water content and the presence of (α + β) phase in Ti-6Al-4V alloy caused not uniform etching. With an additional increase in water content, a nanotubular structure is formed in the (α + β) phases with different morphological parameters. The anatase TiO2 NTs synthesized with 20 wt% H2O shows an improvement in absorption band that extends into the visible region due the presence of vanadium oxide in the structure and the effective band gap energy (Eg) value of 2.25 eV. The TiO2 NTs electrode also shows a good cycling performance, delivering a reversible capacity of 82 mAh.g−1 (34 μAh.cm−2.μm−1) at 1C rate over 50 cycles.